2021
DOI: 10.1021/jacs.1c10261
|View full text |Cite
|
Sign up to set email alerts
|

Propane Dehydrogenation Catalyzed by Isolated Pt Atoms in ≡SiOZn–OH Nests in Dealuminated Zeolite Beta

Abstract: Atomically dispersed noble metal catalysts have drawn wide attention as candidates to replace supported metal clusters and metal nanoparticles. Atomic dispersion can offer unique chemical properties as well as maximum utilization of the expensive metals. Addition of a second metal has been found to help reduce the size of Pt ensembles in bimetallic clusters; however, the stabilization of isolated Pt atoms in small nests of nonprecious metal atoms remains challenging. We now report a novel strategy for the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
153
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 63 publications
9
153
0
Order By: Relevance
“…Moreover, Pt single atoms have been observed together with larger clusters on oxide support, [25] prompting the speculation that they might be able to catalyze propane dehydrogenation (PDH) [24] . Indeed, recent studies have demonstrated the excellent performance of Pt single atoms for PDH, either as single‐atom alloys on oxides [27] or isolated atoms anchored in dealuminated zeolite [28] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pt single atoms have been observed together with larger clusters on oxide support, [25] prompting the speculation that they might be able to catalyze propane dehydrogenation (PDH) [24] . Indeed, recent studies have demonstrated the excellent performance of Pt single atoms for PDH, either as single‐atom alloys on oxides [27] or isolated atoms anchored in dealuminated zeolite [28] …”
Section: Introductionmentioning
confidence: 99%
“…[24] Indeed, recent studies have demonstrated the excellent performance of Pt single atoms for PDH, either as singleatom alloys on oxides [27] or isolated atoms anchored in dealuminated zeolite. [28] The experimental findings of Pt single atoms for PDH have inspired many recent computational studies in exploring Pt single atoms for PDH beyond the oxide supports. Density function theory calculations predicted that single atom Pt on N-doped graphene enhances the Pt's activity in direct dehydrogenation of propane.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other supported metal catalysts, zeolite-supported metal catalysts show significantly improved thermal/hydrothermal stability during catalytic reactions, especially under harsh conditions and unique shape-selective catalytic performances. [35][36][37][38][39][40][41][42][43] Currently, a series of zeolite-supported metal catalysts, such as zeolite-supported monometal catalysts, [44][45][46] zeolite-supported bimetal catalysts, [47][48][49][50] and zeolite-supported single-site catalysts, 51,52 have been developed and exhibited unprecedented long-term stability and ultrahigh selectivity for propylene in PDH reactions (more than 99%), which have attracted widespread attention from both the academic and industrial communities, reflecting their great potential in future practical large-scale applications for PDH reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to find suitable materials, research efforts have concentrated on the use of post transition metal or main group element promoters like Zn [6][7][8][9][10][11][12][13] , B 14,15 , Ga [16][17][18][19][20] , In [21][22][23] and Sn 1,5,24 in combination with varying supports. All these promoters are known to drastically increase the PDH performance compared to monometallic Pt by increasing both selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%